A simple route to synthesize ferromagnetic binary calcium iron pyrophosphate CaFeP2O2 using aqueous-acetone media - Chaiyasith, Pachernchaipat; Ruttanapun, Chesta; Thongkam, Montree; Kongteweelert, Samart; Woramongkonchai, Somsak; Boonchom, Banjong (My University, 2013)
A binary calcium iron pyrophosphate CaFeP2O7 was synthesized by solid state route using the mixing of calcium carbonate, iron metal and phosphoric acid in aqueous-acetone media at 600°C. The XRD datum indicates the formation of CaFeP2O7 phase without the presence of any phase impurities. FTIR result indicates the presence of the P2O7 4- anion in the structure. Sheet-like microparticle of CaFeP2O7 was revealed by SEM. Room temperature magnetization result showed ferromagnetic behavior of the synthesized CaFeP2O7, with saturation-specific magnetization value of 11.067 emu g-1 at 10kOe. The magnetic feature of the synthesized CaFeP2O7 in this work compared with M2P2O7 (M = Ca and Fe), its isotypic (CaMP2O7 (M= Mn and Co) and CFeP2O7 (C= Co and Cu) reported in our previous works is important properties for specific applications. © (2013) Trans Tech Publications, Switzerland.
Keywords: Binary pyrophosphate; CaFeP2O7; Ferromagnetic; Synthesis